Cooperation between C/EBPalpha TBP/TFIIB and SWI/SNF recruiting domains is required for adipocyte differentiation. - Pedersen, T; Kowenz-Leutz, E; Leutz, A; Nerlov, C (2001)
Chromatin remodeling is an important step in promoter activation during cellular lineage commitment and differentiation. We show that the ability of the C/EBPalpha transcription factor to direct adipocyte differentiation of uncommitted fibroblast precursors and to activate SWI/SNF-dependent myeloid-specific genes depends on a domain, C/EBPalpha transactivation element III (TE-III), that binds the SWI/SNF chromatin remodeling complex. TE-III collaborates with C/EBPalpha TBP/TFIIB interaction motifs during induction of adipogenesis and adipocyte-specific gene expression. These results indicate that C/EBPalpha acts as a lineage-instructive transcription factor through SWI/SNF-dependent modification of the chromatin structure of lineage-specific genes, followed by direct promoter activation via recruitment of the basal transcription-initiation complex, and provide a mechanism by which C/EBPalpha can mediate differentiation along multiple cellular lineages.